Pelatihan Peningkatan Kapasitas Guru Madrasah dalam Implementasi Pembelajaran Berbasis Literasi dan Numerasi - Hanifah Noviandari; Anisa Safitri; Alya Hasna Hanifa (Elsalima (Salam Institute), 2025)
The low competence of madrasah teachers in implementing literacy-based learning and numeracy is a significant challenge in improving the quality of madrasah education in the 21st century learning era. The purpose of this service activity is to increase the capacity of madrasah teachers in designing, implementing, and evaluating contextual literacy and numeracy-based learning in accordance with the characteristics of madrasah students. The implementation method uses a participatory training approach with interactive lecture techniques, group discussions, practical workshops, and direct mentoring. The activity was held for one day on January 14, 2025 involving 50 madrasah teachers from various categories in Dlingo District, Bantul Regency. The results showed a significant increase in understanding of literacy and numeracy concepts by 76%, learning design skills increased by 72%, and implementation skills increased by 68%. The key challenges identified include limited learning resources, lack of ongoing training, and technology gaps. The impact of the training resulted in an innovative learning model that can be applied sustainably with the support of a mentoring system between teachers. The conclusion shows that this training has succeeded in improving the pedagogic competence of madrasah teachers and making a real contribution to the achievement of student literacy and numeracy targets in supporting the improvement of the quality of madrasah education in the 21st century learning era.